PERKEMBANGAN BIOSKOP DI KOTA YOGYAKARTA 1948 â 1990-AN - , ARYASA BONNY BINTORO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper discusses about development of cinemas in the city of Yogyakarta after Indonesian independence until 1990s where the cinemas begin to close one by one. The existence of cinema halls has become a entertainment facility for the public and film lovers. Theaters such as Permata, Indra, Yogya, Empire, and Mataram reached its successfulness with showing import and national movies which is liked by the audiences. The development of the cinemas is divided into several phases that follow on the circumstances at that time, i.e. the revival of cinemas, survive in tough times phase, phase of glory, and the deterioration phase. This business is also encountered difficulties that could lead to the collapse of a cinema. These several factors such as the appearance of television, the presence of cineplex, and film distribution monopoly. This research was conducted using the historical method using book sources, oral sources, and news sources which are obtained from the local newspaper.